Cánones estéticos, funcionales y filosóficos en la arquitectura de las antiguas colonias: la escuela de la Bauhaus - Cianci, Maria Grazia (2018)
2019 is the year of the centenary of the foundation of the Bauhaus. A school, first of applied arts and then of architecture and design that has marked the architectural style and costumes of a century through its masters and students. The Department of Architecture of the Roma Tre University to celebrate the anniversary has implemented a series of multidisciplinary educational research. The research is based on an analysis of this style and how it has spread throughout the world mainly due to political reasons. Specifically, we analyze the way in which the Bauhaus style has developed in the surrounding area far from where it was born and how it has assimilated historical and architectural traditions and styles.